Pyridoxamine Attenuates Doxorubicin-Induced Cardiomyopathy without Affecting Its Antitumor Effect on Rat Mammary Tumor Cells - Sibren Haesen; Eline Verghote; Ellen Heeren; Esther Wolfs; Dorien Deluyker; Virginie Bito (Cells, 2024)
Doxorubicin (DOX) is commonly used in cancer treatment but associated with cardiotoxicity. Pyridoxamine (PM), a vitamin B6 derivative, could be a cardioprotectant. This study investigated the effect of PM on DOX cardiotoxicity and DOX antitumor effectiveness. Sprague Dawley rats were treated intravenously with DOX (2 mg/kg/week) or saline over eight weeks. Two other groups received PM via oral intake (1 g/L in water bottles) next to DOX or saline. Echocardiography was performed after eight weeks. PM treatment significantly attenuated the DOX-induced reduction in left ventricular ejection fraction (72 ± 2% vs. 58 ± 3% in DOX; p < 0.001) and increase in left ventricular end-systolic volume (0.24 ± 0.02 µL/cm2 vs. 0.38 ± 0.03 µL/cm2 in DOX; p < 0.0001). Additionally, LA7 tumor cells were exposed to DOX, PM, or DOX and PM for 24 h, 48 h, and 72 h. Cell viability, proliferation, cytotoxicity, and apoptosis were assessed. DOX significantly reduced LA7 cell viability and proliferation (p < 0.0001) and increased cytotoxicity (p < 0.05) and cleaved caspase-3 (p < 0.001). Concomitant PM treatment did not alter the DOX effect on LA7 cells. In conclusion, PM attenuated DOX-induced cardiomyopathy in vivo without affecting the antitumor effect of DOX in vitro, highlighting PM as a promising cardioprotectant for DOX-induced cardiotoxicity.